Brewing Technology - Kanauchi, Makoto (IntechOpen, 2017)
Many alcoholic beverages produced using various methods are consumed throughout the world. Alcoholic beverages made by brewing cereals, such as beer and Japanese sake, are extremely popular. Brewing them requires a complicated process by which the cereal must be saccharified using enzymes such as amylase. For example, with beer brewing, malt enzymes are used for saccharification. By germination, malt is made from barley to produce enzymes. Finally, wort is made by processing at higher temperatures using malt. The actual techniques require high-level skills. In this book, the discussion encompasses leading-edge brewing technology with fermentation using a non-Saccharomyces starter, healthy uses of spent grain from brewing processes, and an electronic nose for quality control, but it also includes descriptions of local traditional alcoholic beverages of Korea and Cameroon.